Precursors to 16S and 23S ribosomal RNA from a ribonuclear III-strain of Escherichia coli contain intact RNase III processing sites. - Gegenheimer, P (1980)
Escherichia coli cells lacking the ribosomal RNA processing enzyme RNase III do no excise the normal RNA precursors p16a (17S) and p23a from nascent rRNA transcripts. These cells produce, instead, slightly larger p16b and p23b precursors. Digestion of p16b or p23b rRNA with RNases A plus T1 yields double-stranded fragments composed of sequences, located at both the 5' and the 3' end regions of the molecules. The terminal duplex, or stem, of p16b contains sequences surrounding the site of RNase III processing which is wild-type cells produces p16a rRNA: the p23b stem likewise contains an intact RNase III cleavage site. The results confirm our earlier prediction for the structure of rRNA transcripts, and also yield a definite secondary structure for the p16 stem, which was not uniquely determined by the corresponding DNA sequence. These experiments demonstrate the absence of significant RNase III processing activity in rnc-105 strains of E. coli, and implicate the participation of another endonuclease(s) in rRNA processing in mutant and wild-type cells.